Mapping the Epileptogenic Landscape: A Multimodal MRI Study in Drug-Resistant Epilepsy Patients in India - Katherine, Elsha (Sriwijaya Journal of Radiology and Imaging Research, 2024)
Introduction: Drug-resistant epilepsy (DRE) poses a significant challenge to patient management, necessitating precise localization of the epileptogenic zone (EZ) for potential surgical intervention. This study aims to evaluate the utility of multimodal MRI techniques in delineating the EZ in DRE patients in India. Methods: A retrospective analysis was conducted on 50 DRE patients who underwent multimodal MRI evaluation, including high-resolution T1-weighted imaging, T2-weighted imaging, fluid-attenuated inversion recovery (FLAIR), diffusion-weighted imaging (DWI), and susceptibility-weighted imaging (SWI), at a tertiary care center in India. MRI findings were correlated with electroencephalography (EEG) and surgical outcomes. Results: MRI abnormalities were detected in 82% of patients. The most common findings included hippocampal sclerosis (34%), focal cortical dysplasia (26%), and gliosis (18%). DWI and SWI revealed subtle abnormalities in 20% of patients not detected on conventional MRI. Concordance between MRI and EEG was observed in 76% of cases. Surgical outcomes were favorable in 70% of patients with complete resection of the MRI-defined EZ. Conclusion: Multimodal MRI is a valuable tool for mapping the epileptogenic landscape in DRE patients. It aids in the identification of subtle abnormalities, enhances the accuracy of EZ localization, and contributes to improved surgical outcomes.